Mechanical and microstructural investigation of multi-layered Inconel 825 wall fabricated using CMT-based WAAM - I. John Solomon; J. Srinivas; S. John Leon; A. Ramesh; I.J. Rohith; T.S. Senthil (Journal of Alloys and Metallurgical Systems)
In this research, a multi-layered wall was produced using the Wire-Arc Additive Manufacturing (WAAM) technique, specifically employing the Cold Metal Transfer (CMT) method with Inconel 825 wire. The optimized CMT-WAAM parameters were identified using multivariate regression analysis. The mechanical and microstructural properties of the wall were assessed in its lower, middle, and upper sections. The tensile properties showed that the ultimate tensile strength (UTS) ranged from 505 MPa to 514 MPa, closely matching that of conventionally wrought Inconel 825 (505–514 MPa). The yield strength (YS) varied from 199 MPa to 207 MPa, while elongation values ranged from 49.7 % to 57.5 %, depending on the section of the wall. A gradual decrease in hardness was observed from the bottom (246.16 Hv) to the top (221.75 Hv) of the wall. Microscopy identified continuous and discontinuous cellular-dendritic microstructures across the sections. Tensile and impact test fractographs revealed a fibrous ductile fracture mode, with SEM images highlighting the presence of Laves phases and micro-voids, particularly in the upper sections. Despite the formation of Laves phases, which can act as crack initiation sites, the mechanical properties of the WAAM-fabricated wall were comparable to those of wrought Inconel 825.